Distribution modeling of nanoparticles for brachytherapy of human eye tumor - Masoudi, S. Farhad (EJNMMI Phys, 2020)
BACKGROUND: Due to their unique properties, gold nanoparticles (GNPs) have been proposed to be used for a wide range of applications, especially for photon radiation therapy. In addition to experimental works, there are worthwhile simulation-based studies focused on the investigation of the effect of parameters governing the dose enhancement due to the presence of GNPs in tissue. In a recently published study, we found that the distribution of GNPs in a single cell plays an important role in nucleus dose enhancement. METHODS: The present work investigates the sensitivity of dose enhancement of a macroscopic phantom to the modeling of GNPs at the cellular level by using the MCNPX Monte Carlo code. A human eye phantom containing the realistic structures and materials was simulated, with a typical tumor located in its corner filled with three different patterns of distribution of GNPs around the nuclei of the cells. The primary photons emit from a COMS eye plaque brachytherapy containing thirteen (131)Cs seeds in the vicinity of the tumor. RESULTS: The study was extended to estimate dose enhancement for various concentration, size, and density of the GNPs accumulated around the nuclei of the tumor. Moreover, the dose delivered to the healthy eye structures for different models has been investigated and discussed. The results show obvious differences between the dose enhancements in the tumor depending on the modeling of GNPs. CONCLUSION: The results emphasized that an appropriate small-scale model for the distribution of GNPs in the cell would be of high importance to estimate the degree of dose enhancement in a macroscopic phantom to provide a trustworthy prediction to move towards clinical application.